Selection index via blup for identifying superior banana varieties in the central region of Goiás - DE ALMEIDA, GABRIELLA QUEIROZ; Silva, Juliana de Oliveira; Resende, Marcos Deon Vilela de; Meneguci, João Luiz Palma; Matos, Glays Rodrigues (Revista Ceres, 2019)
This work evaluated the behavior of 23 superior banana genotypes of the Cavendish, Prata, Prata-Anã, Pacovan, Mysore and Maçã groups, in three production cycles, in the conditions of Central Goiás region, with the objective of identifying the superior genotypes for this region. Fifteen agronomic and productive characteristics were evaluated from the first bloom to the third production cycle. The varieties FHIA-02 (Cavendish group), PA42-44 (Prata Anã group) and FHIA-18 (Prata Anã group) showed the highest earliness of flowering. The varieties Bucanero, FHIA-17 (Cavendish group) and Grande Naine were the most productive. The varieties Grande Naine, FHIA-17 and FHIA-02 had the lowest sizes and varieties FHIA-17, Bucanero and PV79-34 (Pacovan hybrid) had larger circumferences stem. It is suggested, based on the multi-trait selection index, that the FHIA-17, Grande Naine, Bucanero and FHIA-02 varieties should be produced in the central region of Goiás due to their adequate size and high yield.